anti-Tricyclo[4.2.1.1(2,5)]deca-3,7-diene-9-endo,10-endo-diol - Harris, Andria D. (International Union of Crystallography, 2008)
The title compound, C(10)H(12)O(2), was synthesized as a candidate for further functionalization. The asymmetric unit comprises two independent molecules, both of which are situated on a center of symmetry. Both molecules are involved in a network of hydrogen bonding, with each alcohol group participating in one hydrogen bond as a donor and in a second hydrogen bond as an acceptor.